YIELD LOSS ASSESSMENT IN MUNGBEAN [VIGNA RADIATA (L.) WILCZEK] CAUSED BY ANTHRACNOSE [COLLETOTRICHUM TRUNCATUM (SCHW.) ANDRUS AND MOORE] - VANDANA SHUKLA; SANGHMITRA BAGHEL; KRISHNA MARAVI; S. K. SINGH (The Bioscan, 2014)
Mungbean anthracnose caused by Colletotrichum truncatum (Schw.) Andrus and Moore is the most important seed-borne fungal disease which also infects seedlings, stems, petioles, leaves and pods. Investigation on yield loss assessment in mungbean due to anthracnose was conducted under field condition at NDUAT, Faizabad (U.P.) during Kharif 2012-13 using a susceptible variety NDM-1, a moderate susceptible variety (Pusa Vishal) and a resistant variety (UPM-98). Field experiment revealed that maximum disease in terms of incidence and severity (70.11 %) occurs on highly susceptible cultivar NDM-1. It causes considerable damage by reducing seed quality and yield. The observations revealed that comparatively lower disease index (8.74 %) with increase in grain (10.9 q/ha) and stalk yield (14.7 q/ha) and also maximum number of pods/plant (20.5) and test weight (37.5 g) of grain was recorded in plots receiving two sprays of carbendazim (0.1%) than untreated plots of resistant cultivars. The losses in yield due to anthracnose have been estimated up to 24-67 per cent. The yield losses are proportional to disease severity and very remarkably depending on the stage of infection, genotype and environmental conditions.